Odpowiedź:
a) ciąg jest stały więc a3=-2
b) a3=12 a5=38
an=a1+(n-1)*r
[tex]\left \{ {{12=a1+(3-1)*r} \atop 38=a1+(5-1)*r}} \right.[/tex]
[tex]\left \{ {{12=a1+2r} \atop {38=a1+4*r}} \right.[/tex]
[tex]\left \{ {{a1=12-2r} \atop {a1=38-4r}} \right.[/tex]
12-2r=38-4r
2r=26
r=13
Podstawiamy do 1 równania
a1=12-26=-14
c)a1=4 a4=32
an=a1*[tex]q^{n-1}[/tex]
a4=a1*[tex]q^{3}[/tex]
32=4*[tex]q^{3}[/tex]
[tex]q^{3}[/tex]=8
q=2
d)Sn=[tex]\frac{a1+an}{2} *n[/tex]
S4=[tex]\frac{a1+a4}{2} *n[/tex]
an=a1+(n-1)*r
a2=11 a4=7
11=a1+r
7=a1+3r
[tex]\left \{ {{a1=11-r} \atop {a1=7-3r}} \right.[/tex]
11-r=7-3r
4=-2r
r=-2
a1=11+2=13
S4=[tex]\frac{13+7}{2} *4[/tex]=40
e)Kożystamy z zależności o ciągu geometrycznym
18²=27*(x+5)
324=27x+135
27x=189
x=7